Student Perceptions Of The Smoke-Free Area (Ktr) Regulations On The Faculty Of Medicine And Health Sciences (Fkik) Campus, University Of Jambi, In 2026 - M. Dicky Dermawan; Dwi Noerjoedianto; M. Ridwan; Budi Aswin; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
The implementation of smoke-free zones on campus still faces significant challenges. This phenomenon indicates that the existence of a policy (stimulus) does not automatically result in uniform compliance (response). These differences in response are heavily influenced by students' perceptions. The objective of this study is to conduct a deeper analysis of students' perceptions regarding the Smoke-Free Zone (SFZ) regulations at the Faculty of Medicine and Health Sciences, University of Jambi. The research method employed a quantitative approach using a survey. The study was conducted at the FKIK UNJA campus within the Public Health program. Results of this study indicated that the majority of respondents were 19 years old, totaling 35 respondents (63.6%). The majority of respondents were female, totaling 48 respondents (87.3%). The majority of respondents were non-smokers or had quit smoking, totaling 53 respondents (96.4%). Most respondents had good knowledge, totaling 47 respondents (85.5%). Most respondents had a positive perception of the implementation of smoke-free zones, totaling 34 respondents (61.8%). Conclusion In general, a high level of knowledge tends to be accompanied by a positive perception of the implementation of smoke-free zones on campus, thereby creating a healthy, smoke-free environment.